1995
DOI: 10.1111/j.1432-1033.1995.tb20347.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Phosphorylation of Cardiac Troponin-I on Its Interactions with Actin and Cardiac Troponin-C

Abstract: It is known that the phosphorylation of two serine residues on the NH2-terminal extension specific to cardiac troponin-I (Tn-I) modulates the calcium-dependent activation of the myofilaments. The process by which this occurs remains an unsolved puzzle. We have applied a dissective approach to study the effect of this phosphorylation on the interactions between Tn-I and its partner proteins, actin and troponin-C (Tn-C). Using N-[14C]ethylmaleimide-labelled Tn-I in sedimentation assays with F-actin, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This could reflect the release of the N-terminal extension from a binding site on TnC and possibly movement toward a binding site on the C-terminal region of TnI for the phosphorylated N-terminal extension. Bisphosphorylation of TnI produces a slight decrease in the affinity of TnI for TnC ( , ). This reduction in affinity could arise directly from the loss of the binding contribution from the phosphorylation switch although there is evidence that phosphorylation of the extension alters the affinity of the C-terminal region of TnI for TnC ().…”
Section: Discussionmentioning
confidence: 99%
“…This could reflect the release of the N-terminal extension from a binding site on TnC and possibly movement toward a binding site on the C-terminal region of TnI for the phosphorylated N-terminal extension. Bisphosphorylation of TnI produces a slight decrease in the affinity of TnI for TnC ( , ). This reduction in affinity could arise directly from the loss of the binding contribution from the phosphorylation switch although there is evidence that phosphorylation of the extension alters the affinity of the C-terminal region of TnI for TnC ().…”
Section: Discussionmentioning
confidence: 99%
“…A similar B helix opening was observed without Ca 2+ binding to the N-domain in the binary complex. Phosphorylation of two serine residues (S23 and S24) in cardiac TnI causes a reduction in Ca 2+ binding affinity in the N-domain of TnC ( ), indicating that the N-terminal region of TnI interacts with the N-domain of TnC. Small angle neutron scattering () and cross-linking () studies suggest the existence of this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the interactions of TnC with TnI and Ca 2+ are crucial for the Ca 2+ control of muscle. Early studies showed that β-adrenergic stimulation of contraction was associated with enhanced phosphorylation of TnI (England, 1976; Solaro et al, 1976), that TnI was bis-phosphorylated at serines 22 and 23 in the cardiac-specific N-terminal extension by PKA (Mittmann et al, 1990; Al-Hillawi et al, 1995; Ayaz-Guner et al, 2009) and that the primary effect of phosphorylation of TnI in vitro was reduced Ca 2+ -sensitivity and faster dissociation of Ca 2+ from TnC (Solaro et al, 1976; Robertson et al, 1982; Zhang et al, 1995; Dong et al, 2007). This can cause an increase in the rate of relaxation (lusitropic response) which is essential when heart rate is increased (Kentish et al, 2001; Layland et al, 2005).…”
Section: Introductionmentioning
confidence: 99%